PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN KARAKTER PEDULI SOSIAL PESERTA DIDIK DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V SD INPRES MANGASA 1 KOTA MAKASSAR - Aini, Nur; Abidah Idrus, Nur; Rahman, Hardianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the role playing method to improve students’ social care character in Indonesian language learning of fifth grade at SD Inpres Mangasa 1 Makassar City. The study used a qualitative approach with classroom action research based on the Kemmis and McTaggart model conducted in two cycles, each consisting of two meetings through planning, implementation, observation, and reflection stages. The subjects were the teacher and 24 students. Data were collected through questionnaires, observation, and documentation, and analyzed descriptively using questionnaire and observation results. The results showed that teacher and student activity increased from the first cycle to the second. Furthermore, social care character based on observations and questionnaires, also showed a significant increase from the first to the second cycle. Therefore, the role playing method can improve students social care character.